The Circular Economy – A Lever for the Transition to Sustainable Consumption - Ivanova, Vania (Research Papers, 2022)
In the newly adopted ambitious strategy of the EU – European Green Pact >European Green Deal , economic growth, fair ecological transition, resource efficient >resource-efficient and low carbon economy are the key focuses for development in the next decade. Building on the UN’s new Sustainable Development Goals (SDGs), this transformation goes through a complete change in the business models of companies and households. The aim of this paper is to show the possibility of the circular economy concept becoming a lever for a transition towards sustainable consumption. The relationship between household waste generation and economic growth in Bulgaria and France is investigated. Practices of food waste prevention and efficient reuse are shown. Full secondary data and descriptive analysis are used. The results show an existing significant potential to reduce the proportion of household waste, increase reuse. Certain deficits in the regulatory and institutional framework in Bulgaria are also highlighted.